Fibrinolytic Activity in Peripheral Atherosclerosis in the Elderly - van der Bom, Johanna G.; Bots, Michiel L.; Haverkate, Frits; Meyer, Piet; Hofman, Albert; Grobbee, Diederick E.; Kluft, Cornelis (Thrombosis and Haemostasis, 1999)
Increased concentrations of plasminogen activator inhibitor type 1 (PAI-1) and of D-dimer have jointly been found in subjects with cardiovascular disease. To understand this apparent paradox of increased inhibition of fibrinolysis (high PAI-1) combined with increased fibrinolytic activity (high D-dimer), we examined the relation between D-dimer, PAI-1 and the activator of fibrinolysis, tissue type plasminogen activator (t-PA) in subjects with varying severity of peripheral atherosclerosis. In 325 subjects selected from the Rotterdam Study, a cohort of 7983 men and women aged 55 years and over, the ankle to brachial systolic blood pressure ratio, t-PA antigen and activity, PAI-1 antigen and D-dimer were measured.T-PA antigen and t-PA activity were, independent from each other, increased with degree of atherosclerosis; t-PA antigen increased with 3.5 ng/ml (SE 1.7, p = 0.04) and t-PA activity with 0.46 IU/ml (0.20, p = 0.02) per unit decrease in ankle to brachial pressure ratio (i.e. increase in atherosclerosis). PAI-1 antigen was not related to atherosclerosis. More marked atherosclerosis was associated with increased D-dimer, mainly in subgroups with PAI-1 antigen below 50 ng/ml, t-PA antigen below 10 ng/ml, or t-PA activity above 1.5 IU/ml. In contrast to current beliefs, we found that only a fraction of the variation of t-PA antigen was due to the variation in circulating PAI-1 antigen. A slight positive association was observed between t-PA antigen and D-dimer. PAI-1 and t-PA activity were not associated with D-dimer concentration.In conclusion, in subjects with peripheral atherosclerosis PAI-1 antigen is not increased, but low PAI-1 levels (and possibly also low levels of t-PA antigen and high levels of t-PA activity) appear to be required to increase circulating D-dimer. This suggests that increased D-dimer levels in subjects with atherosclerosis do not reflect increased inhibition, but rather reflect increased fibrinolysis.